Tin-silver filled flexible conductive adhesive and preparation method thereof
By using acrylic modified polyether prepolymer and mixed conductive filler of tin nanowires and floral silver powder in the conductive glue material, the problems of hard brittleness after curing and reduced conductivity after bending are solved, and a combination of high flexibility and excellent conductivity is achieved.
Patent Information
- Application Number
- CN202411902250.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the conductive properties of acrylic resin conductive adhesive materials have been significantly reduced after curing and after bending.
Flexible polymer matrix material is obtained by block reaction using acrylic acid, aliphatic acrylic epoxy resin prepolymer and acrylic polyether prepolymer, and low-melting point tin nanomaterial and high-conductive floral silver powder material are selected as conductive fillers.
It improves the flexibility and conductivity of the conductive adhesive material, ensures that the conductive adhesive can maintain excellent conductivity after repeated bending, and at the same time improves the bonding strength and practicality, making it suitable for assembly line mass production in the field of flexible electronics.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer conductive adhesives, and in particular to a thermally cured tin-silver filled flexible conductive adhesive and a preparation method thereof. Background Art
[0002] As electronic products develop towards miniaturization, precision and greenness, traditional tin-lead soldering materials are increasingly difficult to meet the needs in integrated circuit and microelectronic connection applications due to their low precision, poor line resolution, serious pollution and high soldering temperature. Therefore, the development of high-performance conductive adhesive connection materials with advantages such as high line resolution, low pollution and low curing temperature has gradually become one of the mainstream development directions.
[0003] Since acrylic resin contains an appropriate amount of carbon-carbon double bonds in its molecules, it can be effectively cured by ultraviolet light, heating or photothermal dual curing process. (For example, Chinese patent CN112358841 A discloses a flexible UV-heat-cured transparent conductive adhesive and its preparation method, and Chinese patent CN113912824A discloses a modified epoxy acrylate prepolymer, a preparation method of photothermal dual curing conductive adhesive). Epoxy acrylic resin has the advantages of good chemical corrosion resistance, strong adhesion, and good film-forming properties. It is a conductive adhesive resin matrix material that can be produced at low cost and in large quantities. However, acrylic resin is brittle and has poor impact resistance after curing, which greatly limits the practical application and promotion of acrylic resin in flexible conductive adhesive materials. At present, the commonly used conductive adhesive material is to achieve the conductive function by filling conductive powder in the polymer matrix material. The conductive adhesive material after curing has poor flexibility and the conductive performance of the conductive adhesive material decreases significantly after bending, which limits the application of conductive adhesive in new flexible electronic products. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned defects in the prior art and provide a tin-silver flexible conductive adhesive and a preparation method, which solves the technical problems in the prior art that the acrylic resin conductive adhesive material is hard and brittle after curing and the conductive performance decreases significantly after bending.
[0005] To achieve the above object, the present invention provides a tin-silver filled flexible conductive adhesive, the following components are calculated by weight fraction:
[0006]
[0007] The acrylic acid modified polyether prepolymer is an acrylic acid terminated polyether, and its number average molecular weight is 400-800.
[0008] In the above technical solution, the acrylic epoxy resin prepolymer is prepared by catalysis of 32 parts of epichlorohydrin, 10 parts of glycerol, 30 parts of acrylic acid, 1 part of inhibitor p-hydroxyanisole and 0.2 parts of catalyst by mass.
[0009] In the above technical solution, the acrylic epoxy resin prepolymer has a hydroxyl content of 10.7% and a vinyl content of 22%.
[0010] In the above technical solution, the conductive filler is a mixture of tin nanowires and flower-shaped silver powder.
[0011] In the above technical solution, the mass ratio of the tin nanowires to the flower-shaped silver powder is 1:3.
[0012] In the above technical solution, the length of the tin nanowire is about 100-300 nm, and the particle size of the flower-shaped silver powder is 0.2-2 μm.
[0013] In the above technical solution, the thermal initiator is tert-butyl peroxide-2-ethylhexanoate.
[0014] In the above technical solution, the preferred thermal curing temperature when the thermal initiator is cured is 90-180°C.
[0015] In the above technical solution, the acrylic acid-modified polyether prepolymer comprises: acrylic acid-modified ethylene oxide and / or propylene oxide, and the number average molecular weight thereof is 400-800.
[0016] The present technical solution also provides a method for preparing the tin-silver filled flexible conductive adhesive in the above technical solution, comprising the following steps:
[0017] (1) Add 20-40 parts of acrylic epoxy resin prepolymer, 5-10 parts of acrylic acid, and 0.5-3 parts of thermal initiator into a reaction kettle, and stir at room temperature for 10 minutes until the mixture is uniform.
[0018] (2) Then, add 30-50 parts of acrylic acid modified polyether prepolymer and stir at high speed for 10 minutes.
[0019] (3) Add 10-30 parts of mixed conductive filler, stir at high speed and perform ultrasonic treatment to mix and grind evenly to obtain a conductive adhesive paste material.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention obtains a flexible polymer matrix material by block reaction of acrylic acid, aliphatic acrylic epoxy resin prepolymer and acrylic polyether prepolymer, and improves the problem of high brittleness of acrylic resin material after curing through flexible segments. By selecting low melting point tin nanomaterials and high conductivity flower-shaped silver powder materials as conductive fillers, it is beneficial to improve the acrylic conductive adhesive material to maintain relatively good conductive performance after repeated bending; at the same time, the conductive adhesive has the characteristics of simple preparation process, strong practicality, high bonding strength, good conductive performance, and repeatable bending, and is suitable for assembly line batch production in the field of flexible electronics. DETAILED DESCRIPTION
[0024] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0025] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0026] The present embodiment provides a tin-silver filled flexible conductive adhesive, the following components are calculated by weight: 20-40 parts of acrylic epoxy resin prepolymer, 30-50 parts of acrylic modified polyether prepolymer, 5-10 parts of acrylic acid, 10-30 parts of conductive filler, and 0.5-3 parts of thermal initiator. The acrylic epoxy resin prepolymer is prepared by 32 parts of epichlorohydrin, 10 parts of glycerol, 30 parts of acrylic acid, 1 part of inhibitor p-hydroxyanisole and 0.2 parts of catalyst by mass, wherein the acrylic modified polyether prepolymer comprises: acrylic modified ethylene oxide and / or propylene oxide, whose number average molecular weight is 400-800; the acrylic modified polyether prepolymer imparts good flexibility to the conductive adhesive matrix material through the polyether molecular chain structure, functionalizes and caps the polyether molecules through acrylic acid, and subsequently polymerizes with acrylic epoxy resin through free radical reaction to improve the flexibility of acrylic epoxy resin, wherein the acrylic modified polyether resin has a hydroxyl content of 10.7%, a vinyl content of 22%, and a number average molecular weight of 400-800; wherein the chemical formula of the acrylic epoxy resin prepolymer is:
[0027]
[0028] The chemical formula of acrylic acid modified polyether prepolymer is:
[0029]
[0030] In addition, the conductive filler is preferably tin nanowires and flower-shaped silver powder, wherein the length of the tin nanowires is about 100-300 nm, the particle size of the flower-shaped silver powder is 0.2-2 μm, and the ratio of the tin nanowires to the silver powder is 1: 3. In this embodiment, the thermal initiator is tert-butyl peroxy-2-ethylhexanoate, and the preferred thermal curing temperature during curing is 90-180°C.
[0031] This embodiment also provides a method for preparing the tin-silver filled flexible conductive adhesive in the above technical solution, comprising the following steps:
[0032] (1) Add 20-40 parts of acrylic epoxy resin prepolymer, 5-10 parts of acrylic acid, and 0.5-3 parts of thermal initiator into a reaction kettle, and stir at room temperature for 10 minutes until the mixture is uniform.
[0033] (2) Then, add 30-50 parts of acrylic acid modified polyether prepolymer and stir at high speed for 10 minutes.
[0034] (3) Add 10-30 parts of mixed conductive filler, stir at high speed and perform ultrasonic treatment to mix and grind evenly to obtain a conductive adhesive paste material.
[0035] Example 1: 30g of acrylic epoxy resin prepolymer, 1g of tert-butyl 2-ethylhexanoate and 10g of acrylic monomer are added to a reactor and stirred at room temperature for 10 minutes. 30 parts of acrylic modified polyether prepolymer are added to the mixed matrix material and stirred at high speed for 10 minutes. 10g of mixed conductive filler (containing 200nm nano-tin wire and 1μm flower-shaped silver powder in a mass ratio of 1:3) is added to the above polymer matrix material in two batches, stirred at high speed for 5 minutes, and then ultrasonically treated for 10 minutes (ultrasonic frequency is 20KHz) to obtain the tin-silver filled flexible conductive adhesive paste material of the present invention.
[0036] Example 2: 30g of acrylic epoxy resin prepolymer, 1g of tert-butyl 2-ethylhexanoate and 10g of acrylic monomer are added to a reactor and stirred at room temperature for 10 minutes. 40 parts of acrylic modified polyether prepolymer are added to the mixed matrix material and stirred at high speed for 10 minutes. 10g of mixed conductive filler (containing 200nm nano-tin wire and 1μm flower-shaped silver powder in a mass ratio of 1:3) is added to the above polymer matrix material in two batches, stirred at high speed for 5 minutes, and then ultrasonically treated for 10 minutes (ultrasonic frequency is 20KHz) to obtain the tin-silver filled flexible conductive adhesive paste material of the present invention.
[0037] Example 3: 30g of acrylic epoxy resin prepolymer, 1g of tert-butyl 2-ethylhexanoate and 10g of acrylic monomer are added to a reactor and stirred at room temperature for 10 minutes. 50 parts of acrylic modified polyether prepolymer are added to the mixed matrix material and stirred at high speed for 10 minutes. 10g of mixed conductive filler (containing 200nm nano-tin wire and 1μm flower-shaped silver powder in a mass ratio of 1:3) is added to the above polymer matrix material in two batches, stirred at high speed for 5 minutes, and then ultrasonically treated for 10 minutes (ultrasonic frequency is 20KHz) to obtain the tin-silver filled flexible conductive adhesive paste material of the present invention.
[0038] Example 4: 40g of acrylic epoxy resin prepolymer, 1g of tert-butyl 2-ethylhexanoate and 10g of acrylic monomer are added to a reactor and stirred at room temperature for 10 minutes. 50 parts of acrylic modified polyether prepolymer are added to the mixed matrix material and stirred at high speed for 10 minutes. 10g of mixed conductive filler (containing 200nm nano-tin wire and 1μm flower-shaped silver powder in a mass ratio of 1:3) is added to the above polymer matrix material in two batches, stirred at high speed for 5 minutes, and then ultrasonically treated for 10 minutes (ultrasonic frequency is 20KHz) to obtain the tin-silver filled flexible conductive adhesive paste material of the present invention.
[0039] Example 5
[0040] The difference between this embodiment and Example 2 is that the added amount of the mixed conductive filler is 15 g, and the rest is the same as Example 2.
[0041] Example 6
[0042] The difference between this embodiment and Example 2 is that the added amount of the mixed conductive filler is 20g, and the rest is the same as Example 2.
[0043] Example 7
[0044] The difference between this embodiment and Example 2 is that the added amount of the mixed conductive filler is 25 g, and the rest is the same as Example 2.
[0045] Example 8
[0046] The difference between this embodiment and Example 2 is that the added amount of the mixed conductive filler is 30g, and the rest is the same as Example 2.
[0047] Comparative Example 1
[0048] The difference between this embodiment and Example 2 is that the added amount of the mixed conductive filler is 0 g, and the rest is the same as Example 2.
[0049] Comparative Example 2
[0050] The difference between this embodiment and Example 2 is that the added amount of the mixed conductive filler is 5 g, and the rest is the same as Example 2.
[0051] Comparative Example 3
[0052] The difference between this embodiment and Example 2 is that the added amount of the mixed conductive filler is 35 g, and the rest is the same as Example 2.
[0053] Comparative Example 4
[0054] The difference between this embodiment and Example 2 is that the added amount of the mixed conductive filler is 40 g, and the rest is the same as Example 2.
[0055] Comparative Example 5
[0056] The difference between this embodiment and Example 1 is that the amount of the acrylic acid modified polyether prepolymer is 20 parts, and the rest is the same as Example 1.
[0057] Comparative Example 6
[0058] The difference between this embodiment and Example 1 is that the amount of the acrylic acid modified polyether prepolymer is 10 parts, and the other aspects are the same as those of Example 1.
[0059] Comparative Example 7
[0060] The difference between this embodiment and Example 1 is that the amount of the acrylic acid modified polyether prepolymer is 55 parts, and the rest is the same as Example 1.
[0061] Comparative Example 8
[0062] The difference between this embodiment and Example 1 is that the amount of the acrylic acid modified polyether prepolymer is 60 parts, and the rest is the same as Example 1.
[0063] The volume resistivity comparison test of the heat-cured conductive adhesive of Examples 1-8 was carried out by the following method: the conductive adhesive prepared in the above examples was heat-cured at a temperature of 90-180°C for 10 minutes, and the heat-cured conductive adhesive was placed at room temperature for 1 day before testing.
[0064] Volume resistivity test: Under the conditions of ambient temperature of 25±2℃ and humidity of 60±3%RH, the test is carried out using a four-probe tester according to the inspection standard ASTMD257-2014 Test method for DC resistance or conductivity of insulating materials.
[0065] Table 1 shows the test data of the conductive adhesive film obtained by coating the heat-curing conductive adhesive prepared in Examples 1-8 and Comparative Example 1 on a polyethylene naphthalate (PEN) substrate and curing at 120° C. for 10 minutes.
[0066]
[0067] Table 2 shows the thermal curing conductive adhesive prepared in Example 7 coated on polyethylene naphthalate
[0068]
[0069] The conductive adhesive film was obtained by using a PEN substrate and cured at 90-180°C for 10 minutes.
[0070] In the above table, by comparing Example 2 with Examples 5-8, it can be seen that in the present invention, the content of tin-silver filler in the conductive adhesive has a significant effect on the conductive properties of the conductive adhesive. As the content of the conductive filler increases, the resistivity of the conductive adhesive is significantly improved. The optimal experimental scheme is Example 7.
[0071] By comparing Example 2 with Comparative Examples 1-4, it can be seen that when the content of the tin-silver filler in the conductive adhesive is 0, the resistivity of the conductive adhesive is 3.2*10 12 Ω.cm, which is equivalent to polyepoxy resin and is an insulator. When the content of tin-silver filler in the conductive glue increases to 5g, the resistivity of the conductive glue is significantly improved; when the content of tin-silver filler in the conductive glue exceeds the range value of the present invention, the resistivity of the conductive glue remains basically unchanged, which is about 1.5*10 -4 Ω.cm, indicating that when the conductive filler content exceeds a certain equivalent value, an effective conductive network structure can be formed.
[0072] By comparing Example 1 with Examples 2-3, it can be seen that in the present invention, the flexible segments of the conductive adhesive matrix material have a significant effect on the resistance performance of the conductive adhesive after curing and bending. As the content of the flexible segments in the conductive adhesive matrix material increases, the degree of decrease in the resistivity of the conductive adhesive after bending gradually decreases.
[0073] By comparing Example 1 with Examples 2-3, it can be seen that in the present invention, the flexible segments of the conductive adhesive matrix material have a significant effect on the resistance performance of the conductive adhesive after curing and bending. As the content of the flexible segments in the conductive adhesive matrix material increases, the degree of decrease in the resistivity of the conductive adhesive after bending gradually decreases.
[0074] By comparing Example 1 and Comparative Examples 5-8, it can be seen that when the content of the acrylic acid modified polyether prepolymer is lower than the set range value of the present invention, repeated bending of the conductive adhesive after curing will cause the resistivity of the conductive adhesive to increase significantly. When the content of the acrylic acid modified polyether prepolymer is higher than the set range value of the present invention, repeated bending of the conductive adhesive after curing has little effect on the resistivity of the conductive adhesive. The introduction of surface flexible chain segments can effectively improve the conductive performance of the conductive adhesive after bending.
[0075] By comparing the resistance properties of the conductive adhesive cured at different temperatures in Example 7, it can be seen that as the curing temperature of the conductive adhesive increases, the resistivity of the conductive adhesive gradually decreases, and the higher the curing temperature, the smaller the impact of the conductive adhesive on resistance after bending.
[0076] From the above results, it can be seen that the performance of acrylic resin conductive adhesive modified with polyether flexible chain segments is different, but the higher the content of flexible polyether chain segments, the better the conductive performance of the conductive adhesive after bending, and as the curing temperature increases, the resistivity increase of the conductive adhesive after bending slows down. Example 7 is the photocurable conductive adhesive with the best comprehensive performance among the existing examples.
[0077] The various indices of the above-mentioned embodiments can be combined arbitrarily. To make the description concise, this patent does not describe all possible combinations of the various indices in the embodiments. However, as long as there is no contradiction in the combination of these indices, they should be considered to be within the scope of this specification.
[0078] The above-mentioned embodiments are only a part of several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of this patent. It should be pointed out that for ordinary technicians in this field, several improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A tin-silver filled flexible conductive adhesive, characterized in that: The following components are calculated by weight fraction: The acrylic acid modified polyether prepolymer is an acrylic acid terminated polyether, and its number average molecular weight is 400-800.
2. The tin-silver filled flexible conductive adhesive according to claim 1, characterized in that: The acrylic epoxy resin prepolymer is prepared by catalysis of 32 parts of epichlorohydrin, 10 parts of glycerol, 30 parts of acrylic acid, 1 part of polymerization inhibitor p-hydroxyanisole and 0.2 parts of catalyst by mass.
3. The tin-silver filled flexible conductive adhesive according to claim 2, characterized in that: The acrylic epoxy resin prepolymer has a hydroxyl content of 10.7% and a vinyl content of 22%.
4. The tin-silver filled flexible conductive adhesive according to claim 1, characterized in that: The conductive filler is a mixture of tin nanowires and flower-shaped silver powder.
5. The tin-silver filled flexible conductive adhesive according to claim 4, characterized in that: The mass ratio of the tin nanowires to the flower-shaped silver powder is 1:
3.
6. The tin-silver filled flexible conductive adhesive according to claim 5, characterized in that: The length of the tin nanowire is about 100-300 nm, and the particle size of the flower-shaped silver powder is 0.2-2 μm.
7. The tin-silver filled flexible conductive adhesive according to claim 1, characterized in that: The thermal initiator is tert-butyl peroxide-2-ethylhexanoate.
8. The tin-silver filled flexible conductive adhesive according to claim 7, characterized in that: The thermal curing temperature of the thermal initiator during curing is 90-180°C.
9. The tin-silver filled flexible conductive adhesive according to claim 1, characterized in that: The acrylic acid modified polyether prepolymer comprises: acrylic acid modified ethylene oxide and / or propylene oxide, and the number average molecular weight thereof is 400-800.
10. A method for preparing the light-curing epoxy acrylic resin conductive adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Add 20-40 parts of acrylic epoxy resin prepolymer, 5-10 parts of acrylic acid, and 0.5-3 parts of thermal initiator into a reaction kettle, and stir at room temperature for 10 minutes until the mixture is uniform. (2) Then, add 30-50 parts of acrylic acid modified polyether prepolymer and stir at high speed for 10 minutes. (3) Add 10-30 parts of mixed conductive filler, stir at high speed and perform ultrasonic treatment to mix and grind evenly to obtain a conductive adhesive paste material.
Citation Information
Patent Citations
Flexible UV-thermal dual-curing transparent conductive adhesive and preparation method thereof
CN112358841A
Modified epoxy acrylate prepolymer, photo-thermal dual-curing conductive adhesive and preparation method of photo-thermal dual-curing conductive adhesive
CN113912824A